KOMPETENSI KEPRIBADIAN GURU PENDIDIKAN AGAMA ISLAM DALAM MEMBINA AKHLAK PESERTA DIDIK - Edi Iklan Jaya (UNISAN JURNAL, 2024)
This exploration means to depict the ability of Islamic strict schooling educators in creating understudy ethics at SMA Negeri 1 Penukal. This examination utilizes a subjective methodology with enlightening strategies. Information assortment was helped out through perception, meetings and documentation. The exploration subjects were Islamic strict schooling educators and understudies in grades X and XI. Information were dissected through information decrease, information show, and reaching inferences. The aftereffects of the examination show that the Islamic Strict Training educator at SMA Negeri 1 Penukal has great character ability in fostering understudies’ ethics. In light of understudy evaluations, most educators have an uplifting outlook, are well mannered, and regard variety in instructing. They additionally can impart moral and moral qualities in understudies. Aside from that, the exploration results show that there are a few factors that impact the character capability of Islamic Strict Schooling instructors, including the preparation and training got, showing experience, and the educator’s own character. Quality preparation and schooling can assist instructors with working on their ability, while showing experience can assist educators with creating abilities and certainty. An educator’s positive character and trustworthiness is likewise extremely persuasive in fostering understudies’ ethics